Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan dengan Dimediasi Variabel Motivasi - Puji Santoso; Heru Baskoro (Jurnal Simki Economic, 2024)
This research aims to determine the effect of Leadership Style and Work Environment on Employee Performance mediated by Motivation variables. The population used in this research were employees in the quality control department at an PT. XYZ instant food company in Gresik district. The sample in this research was 54 respondents with a quantitative approach, using non-probability sampling techniques. This data was taken using a questionnaire which was distributed directly to respondents. After the questionnaire was collected, the data was tabulated using Microsoft Excel and analyzed using Smart PLS 4. The results of this research show that Leadership Style has a significant effect on Employee Performance, Work Environment has a significant effect on Employee Performance, Motivation has a significant effect on Employee Performance, Leadership Style has a significant effect on Motivation, Work Environment has a significant effect on Motivation.The Motivation variable succeeded in mediating the effect of the Leadership Style and Work Environment variables on employee performance.